Therapy Of Post-Covid Fibrotic Changes (Eurasian Medical Research Periodical, 2023)
Among the extensive manifestations of post-covid syndrome, cough is often found. Most researchers interpret its nature as post-infectious. In some patients, postinfectious cough becomes productive and effective treatment requires combined mucoactive therapy. Also, since the beginning of the pandemic, enough clinical observations of spontaneous pneumothorax have accumulated in the literature. The risk of this complication is present even in patients who are not burdened with chronic lung diseases, as well as in spontaneous breathing. The study of the mechanisms of development of spontaneous pneumothorax in COVID-19 is necessary for the development of further therapeutic and preventive measures. Traction bronchiectasis occurs in 27–52.5% of cases of novel coronavirus infection (NCI).